STUDI EVALUATIF TENTANG KEBERADAAN SEKOLAH PROGRAM BAKAT ISTIMEWA BERDASARKAN 8 STANDAR NASIONAL PENDIDIKAN TINGKAT SMP/MTS - Indahwati, Nanik; Suroto, Suroto; Aripin, Zainul (Journal of Sport Science and Education, 2017)
The purpose of this research is to know clearly about the existence of special talent program schools (especially sports) by analyzing and evaluating based on 8 national standard of junior high school / MTs education which includes graduate competency standard, content standard, process standard, educator standard and educational staff , Facilities and infrastructure standards,management standards, financing standards, and educational assessment standards. The research was conducted in Madrasah Tsanawiyah Negeri Malang III by using qualitative approach, where the data source was obtained from: informant, covering principal, vice curriculum, vice facilities and Infrastructure, vice treasurer, head of Special Talent Program, teacher and trainer, and student) and document. Data validity using triangulation. While the research results using interactive model analysis techniques that include data collection, data reduction, data presentation, and conclusion.Based on the results of the research findings, it can be concluded that: (1) The existence of Special Talent Program Schools in Madrasah Tsanawiyah Negeri Malang III from the beginning held in the academic year 2013/2014 until 2016/2017 has increased in the fulfillment of facilities and infrastructure for students Special talent, though there is still something to be improved regarding the field used in the training process. While in the Standards Assessment is still less specific in the formulation of competence. This can be seen from the format of report cards that are not adjusted to the sport chosen by the students, (2) the existence of Special Talent Program School in MadrasahTsanawiyah Negeri Malang III improve the quality of the students especially in the field of nonacademic sports. This can be seen from the achievements generated both at the district, provincial and national levels obtained by madrasah through learners who pursue special talent programs.